Leveraging patient experience data to guide medicines development, regulation, access decisions and clinical care in the EU - Almeida, Diogo; Umuhire, Denise; Gonzalez-Quevedo, Rosa; António, Ana; Burgos, Juan Garcia; Verpillat, Patrice; Bere, Nathalie; Sepodes, Bruno; Torre, Carla (Frontiers in Medicine, 2024)
Patient experience data (PED), provided by patients/their carers without interpretation by clinicians, directly capture what matters more to patients on their medical condition, treatment and impact of healthcare. PED can be collected through different methodologies and these need to be robust and validated for its intended use. Medicine regulators are increasingly encouraging stakeholders to generate, collect and submit PED to support both scientific advice in development programs and regulatory decisions on the approval and use of these medicines. This article reviews the existing definitions and types of PED and demonstrate the potential for use in different settings of medicines’ life cycle, focusing on Patient-Reported Outcomes (PRO) and Patient Preferences (PP). Furthermore, it addresses some challenges and opportunities, alluding to important regulatory guidance that has been published, methodological aspects and digitalization, highlighting the lack of guidance as a key hurdle to achieve more systematic inclusion of PED in regulatory submissions. In addition, the article discusses opportunities at European and global level that could be implemented to leverage PED use. New digital tools that allow patients to collect PED in real time could also contribute to these advances, but it is equally important not to overlook the challenges they entail. The numerous and relevant initiatives being developed by various stakeholders in this field, including regulators, show their confidence in PED’s value and create an ideal moment to address challenges and consolidate PED use across medicines’ life cycle.